Assessing the Impact of International Travel Experiences on Sexual Health of Young Canadian Adults - Gareau, Emmanuelle (Université d'Ottawa / University of Ottawa, 2021)
Over the past two decades, the popularity of international travel has increased dramatically, especially among young adults. The behaviours of travellers abroad may differ from their behaviours at-home, especially among young adults who tend to take more risks regarding their sexual health. This thesis therefore explored the impact of travel on the sexual health of young Canadian adults from the perspectives of young Canadian travellers themselves, as well as of the experiences of travel health sector key informants. Our results indicate that although young Canadian adults are less sexually active abroad, their sexual health remains at-risk, a perspective shared by interviewed key informants. This thesis reiterates the importance of sexual health promotion among young Canadian adults, particularly those travelling abroad, through comprehensive, positive and inclusive sexuality education as well as through pre- and post-travel interventions individually adapted to the needs and to the risk and protective factors of each traveller.
Keywords: travel; sexual health; youth; young adults; risk behaviours; sexual practices; sexuality; travel organization; travel clinic; travel medicine